Radiation safety considerations for the use of radium-224-calciumcarbonate-microparticles in patients with peritoneal metastasis - Grønningsæter, Simen Rykkje; Blakkisrud, Johan; Selboe, Silje; Revheim, Mona-Elisabeth; Bruland, Øyvind Sverre; Bønsdorff, Tina Bjørnlund; Larsen, Stein Gunnar; Stokke, Caroline (Frontiers in Medicine, 2023)
Aim: Two ongoing phase I studies are investigating the use of radium-224 adsorbed to calcium carbonate micro particles (224Ra-CaCO3-MP) to treat peritoneal metastasis originating from colorectal or ovarian cancer. The aim of this work was to study the level of radiation exposure from the patients to workers at the hospital, carers and members of the public. Method: Six patients from the phase 1 trial in patients with colorectal cancer were included in this study. Two days after cytoreductive surgery, they were injected with 7 MBq of 224Ra-CaCO3-MP. At approximately 3, 24 and 120 hours after injection, the patients underwent measurements with an ionization chamber and a scintillator-based iodide detector, and whole body gamma camera imaging. The patient was modelled as a planar source to calculate dose rate as a function of distance. Scenarios varying in duration and distance from the patient were created to estimate the potential effective doses from external exposure. Urine and blood samples were collected at approximately 3, 6, 24, 48 and 120 hours after injection of 224Ra-CaCO3-MP, to estimate the activity concentration of 224Ra and 212Pb. Results: The patients’ median effective whole-body half-life of 224Ra-CaCO3-MP ranged from 2.6-3.5 days, with a mean value of 3.0 days. In the scenarios with exposure at the hospital (first 8 days), sporadic patient contact resulted in a range of 3.9-6.8 μSv per patient, and daily contact resulted in 4.3-31.3 μSv depending on the scenario. After discharge from the hospital, at day 8, the highest effective dose was received by those with close daily contact; 18.7-83.0 μSv. The highest activity concentrations of 224Ra and 212Pb in urine and blood were found within six hours, with maximum values of 70 Bq/g for 224Ra and 628 Bq/g for 212Pb. Conclusion: The number of patients treated with 224Ra-CaCO3-MP that a single hospital worker -involved in extensive care- can receive per year, before effective doses of 6 mSv from external exposure is exceeded, is in the order of 200-400. Members of the public and family members are expected to receive well below 0.25 mSv, and therefore, no restrictions to reduce external exposure should be required.